Profil Keluarga Tunarungu di Bungus Teluk Kabung - Yulia Syaputri, Rahmatul; Irdamurni, Irdamurni (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2019)
Every parent who has a child would want to nurture and educate him, as well as families who have limitations or have special needs, especially in deaf families, this study explains the profile of deaf families who live in the Bungung Bay Subdistrict of Kabung Bay, the family numbered seven people, among them there was a father, mother and five other children and all of them were hearing impaired, living in remote and without electricity. This family lives with various limitations, including hearing and economic limitations, they live independently and help one another. This research will reveal the family tree, faktors causing disability, environmental perception and interaction of the deaf family in the environment. This research uses a case study method with a qualitative approach. the results show that this family is a very friendly and polite family with everyone. while the faktors that cause disability are due to hereditary faktors and are supported by environmental faktors. this is because this family lives in a remote place and far from the community. people's perception of this family is very good and they communicate using oral language and gestures to everyone.